Use of new technologies and promotion of breastfeeding: integrative literature review - Galvão,Dulce Maria Pereira Garcia (2022)
ABSTRACT Objective: To identify the most used social networks and the most consumed contents by women seeking support and further understanding of breastfeeding/breast milk. Data source: An integrative literature review was performed using the Psychology & Behavioral Sciences Collection, MEDLINE Complete, CINAHL Complete, MedicLatina, Academic Search Complete and ERIC databases. The search was conducted in April, 2020. The inclusion criteria were: publications in Portuguese, English or Spanish with several keywords, such as “Breastfeeding”, “Social Networking”, “Social Media”, “Breastfeeding Promotion”, in the title and in the abstract, with the combination of the Boolean operators “AND” and “OR”, in original articles of primary source, which were available in full text and were published between 2015 and 2020. Data synthesis: Out of the 93 articles that were first examined, 10 were used in the descriptive summary. Studies from the United States, Sweden, New Zealand, Brazil, Australia, Indonesia, and Switzerland were included in the review. Women were found to use several social networks, which is facilitated by an easy access to the Internet and to its content through several electronic resources, often using more than one device simultaneously. Most issues were universally recognized as some of the most common reasons for interrupting breastfeeding. Conclusions: The analyzed studies show that women seek to clarify their doubts outside the traditional health services’ environment, using Facebook, apps, websites, online videos, podcasts and e-mail. We stress the importance of these support groups for promoting breastfeeding and the need for health professionals to introduce themselves in social networks to reach mothers.